Aspirations, education and inequality in England: insights from the Effective Provision of Pre-school, Primary and Secondary Education Project - Baker, W; Sammons, P; Siraj-Blatchford, I; Sylva, K; Melhuish, E; Taggart, B (Routledge, 2014)
Educational and occupational aspirations have become an important reference point in policy debates about educational inequality. Low aspirations are presented as a major barrier to closing educational attainment gaps and increasing levels of social mobility. Our paper contributes to this on-going debate by presenting data on the educational aspirations of students from the Effective Provision of Pre-School, Primary and Secondary Education Project in England. We analyse factors that help predict students holding high aspirations. Our findings reveal generally high aspirations across all students but also differences by income group and other background factors. We evaluate the significance of these findings for the existing literature and public policy discussions about the importance of raising educational aspirations. In particular, we question the way in which low aspirations are framed by policy-makers as a major problem in debates around educational inequality.